Stigmatizing Attitudes Towards Mental Disorders Among Non-Mental Health Professionals in Six General Hospitals in Hunan Province - Wu, Qiuxia; Luo, Xiaoyang; Chen, Shubao; Qi, Chang; Yang, Winson Fu Zun; Liao, Yanhui; Wang, Xuyi; Tang, Jinsong; Tang, Yiyuan; Liu, Tieqiao (Frontiers in Psychiatry, 2020)
Background: There are few studies about stigma associated with mental disorders among non-mental health professionals in general hospitals in China. This study seeks to explore the mental health-related stigma and the desire for social distance among non-mental health professionals in general hospitals of Hunan Province in China. Methods: The study was carried out with 1123 non-mental health professionals in six general hospitals in Hunan Province by using a questionnaire with case vignette describing either schizophrenia, depression or generalized anxiety disorder (GAD). Questions about the attitudes of participants and other people towards people individuals with mental disorders, and the willingness to contact them were asked. Results: People described in the vignette were considered as dangerous by 84.4% of participants for schizophrenia, 72.0% of participants for depression and 63.1% of participants for GAD. Besides being dangerous, schizophrenia was perceived as unpredictable, with the least likely to be voted for a politician and to be employed. Around 50% of participants believed the problems described in the vignette were due to personal weakness. Over 70% of the non-mental health professionals were not willing to have the people described in the vignette marry into their family. Participants learn about mental health-related knowledge mainly through media, mainly from newspapers. Conclusions: The current study found significant stigma towards people individuals with mental disorders and the desire for social distance among non-mental health professionals in general hospitals in Hunan Province. Anti-stigma interventions should focus on addressing non-mental health professionals’ the beliefs on dangerousness and unpredictability by non-mental health professionals.